Patient‐reported outcomes from a phase 3 randomized controlled trial of inotuzumab ozogamicin versus standard therapy for relapsed/refractory acute lymphoblastic leukemia. Issue 10 (6th March 2018) - Kantarjian, Hagop M.; Su, Yun; Jabbour, Elias J.; Bhattacharyya, Helen; Yan, Eric; Cappelleri, Joseph C.; Marks, David I.
Abstract : BACKGROUND: Inotuzumab ozogamicin (InO), an anti‐CD22 antibody‐calicheamicin conjugate, demonstrated superior clinical activity versus standard‐of‐care (SOC) chemotherapies for relapsed/refractory B‐cell acute lymphoblastic leukemia in the phase 3 randomized controlled INO‐VATE trial. The authors assessed patient‐reported outcomes (PROs) from that study. METHODS: Patients were randomized to receive either InO (1.8 mg/m 2 per cycle for ≤6 cycles) or SOC (fludarabine/cytarabine [ara‐C]/granulocyte colony‐stimulating factor, or ara‐C plus mitoxantrone, or high‐dose ara‐C for ≤4 cycles) and completed the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire and the EuroQoL 5 Dimensions Questionnaires at baseline, on day 1 of each cycle, and at the end of treatment. Treatment differences in PROs were assessed using longitudinal mixed‐effects models with random intercepts and slopes. RESULTS: Questionnaire completion rates in the InO (n = 164) and SOC (n = 162) arms were 85% and 65%, respectively. Baseline scores were similar between arms. Patients who received InO reported better quality of life (QoL), functioning, and symptom scores (except for constipation and emotional functioning). Least‐squares mean (95% confidence interval [CI]) differences in physical, role, and social functioning and in appetite loss were significant (6.9 [95% CI, 1.4‐12.3], 11.4 [95% CI, 3.2‐19.5], 8.4 [95% CI, 0.7‐16.1], and −8.7 [95% CI, −16.0 to −1.4], respectively; all P < .05) and had exceeded the minimally important difference of 5. Mean treatment differences in favor of InO on the EuroQoL visual analog scale and the global health status/QoL, dyspnea, and fatigue scales reached or approached the minimally important difference of 5, although without statistical significance. No dimensions were significantly worse with InO versus SOC. CONCLUSIONS: The current PRO data support the favorable benefit/risk ratio of InO for the treatment of relapsed/refractory acute lymphoblastic leukemia, with superior clinical efficacy and better QoL. Cancer 2018;124:2151‐60 . © 2018 American Cancer Society . Abstract : The superior efficacy of inotuzumab ozogamicin versus standard therapy in patients with relapsed/refractory B‐cell acute lymphoblastic leukemia is accompanied by better patient‐reported outcomes. These findings further support the favorable benefit‐risk profile of inotuzumab ozogamicin in this clinical setting.